The Effect of Political Connections, Managerial Ownership and Liquidity on Tax Aggressiveness - Gloria Br. Ginting, Meta Soledea; Setiawati, Ledy (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This study aims to examine the influence of Political Connections, Managerial Ownership and Liquidity on Tax Aggressiveness in Property and Real Estate Sub-Sector companies Listed on the Indonesia Stock Exchange in 2018-2022. This type of research is quantitative research using secondary data. The sample was determined using the purposive sampling method and obtained data on 150 companies in the Property and Real Estate Sub-Sector listed on the Indonesia Stock Exchange in 2018-2022. The results of this study show that Political Connections have no effect on tax aggressiveness, while Managerial Ownership and Liquidity have a significant negative effect on Tax Aggressiveness